In vitro evaluation of the ZX11 magnesium alloy as potential bone plate: Degradability and mechanical integrity. (1st October 2019) - Hou, Ruiqing; Victoria-Hernandez, Jose; Jiang, Pingli; Willumeit-Römer, Regine; Luthringer-Feyerabend, Bérengère; Yi, Sangbong; Letzig, Dietmar; Feyerabend, Frank
Graphical abstract: Abstract: Considering the excellent biocompatibility of magnesium (Mg) alloys and their better mechanical properties compared to polymer materials, a wrought MgZnCa alloy with low contents of Zn (0.7 wt%) and Ca (0.6 wt%) (ZX11) was developed by twin roll casting (TRC) technology as potential biodegradable bone plates. The degradability and cell response of the ZX11 alloy were evaluated in vitro, as well as the mechanical integrity according to tensile tests after immersion. The results revealed a slightly higher degradation rate for the rolled ZX11, in comparison to that of the annealed one. It was mainly caused by the deformation twins and residual strain stored in the rolled alloy, which also seemed to promote localized degradation, thereby leading to a relatively fast deterioration in mechanical properties, especially the fracture strain/elongation. In contrast, after the annealing treatment, the alloy showed relatively lower strength, yet a lower degradation rate and quite stable elongation during the initial weeks of immersion were observed. More importantly, the ZX11 alloy, regardless of the annealing treatment, showed good in vitro cytocomopatibility regarding human primary osteoblasts. The assessment indicates the rolled alloy as a good choice for implantation sites where relatively high mechanical strength is needed during the early implantation, while the annealed alloy is a potential candidate for the sites which demand stable mechanical integrity during service. Statement of Significance: The development of magnesium alloys as bone implants demands low degradation rate to gain not only a slow hydrogen evolution, but also a stable mechanical integrity during service. The present study develops a micro-alloyed MgZnCa alloy via twin roll casting (TRC) technology. It exhibited limited cytotoxicity, fairly low degradation rate and comparable strength to the reported Mg-1Zn-5Ca alloy which has been used as bone screws in clinical trials, indicating the great potential application as biodegradable bone implants. Furthermore, it showed good mechanical integrity during immersion to support the defect healing. Our results can aid other researchers to evaluate the mechanical integrity of biodegradable materials and to pay more attention to the effect of degradation behaviour on mechanical integrity of materials.